Complete physico-chemical characterisation of foundry waste - Aissaoui, Chahinez; Diliberto, Cécile; Mechling, Jean-Michel; Aranda, Lionel (Environmental technology, 2025)
The manufacture of foundry metal parts generates various types of mineral wastes. Studies mentioned in the literature are mainly interested in the characterisation of foundry sands and their recycling way. The other wastes (finer than sand) are not dealt and are currently stored in landfills without any recycling solution. This paper aims to fill this gap and reports the complete characterisation of foundry wastes (FW) we carried out to find a way of recycling these materials. FWs were characterised by X-ray fluorescence, X-ray diffraction, scanning electron microscopy and thermogravimetry analyses (TGAs). Leaching tests complying with the NF EN 12457-2 standard were also carried out to evaluate the pollution degree of the different waste products. The results of this work that foundries do not produce just one type of waste, but several. Five types of waste were thus analysed and the results indicated in the first step that each sand was unique and in a second one that the two foundries present a certain similarity with regard to their materials. This complete characterisation study will provide a better understanding of their chemical composition and degree of pollution, so that they can be used more effectively in cement blends, which will be the subject of the rest of this study. The reuse of FW in concrete and mortars is possible and can reduce the environmental impact caused by their storage in landfills.